2010
DOI: 10.2754/avb201079010147
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amine Production in Olomouc Curd Cheese (Olomoucké tvarůžky) at Various Storage Conditions

Abstract: The aim of this study was to evaluate the effects of temperature and storage time on the formation of biogenic amines (BAs) in the traditional Czech curd cheese (Olomoucké tvarůžky). Samples were stored for 7 weeks at 5 °C and 20 °C. BAs were studied as dansyl derivatives by the RP-HPLC method with fluorescence detection, histamine was determined using a photodiode array detector. Physical and chemical properties were analyzed as specified by the Czech National Standard, as were the sensory characteristics (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
15
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
6
15
2
1
Order By: Relevance
“…According to Pillonel et al (2003), emmental cheeses contain 8.6–403 mg kg −1 of tyramine. Much higher level of this amine was stated by Standarová et al (2010) in Olomouc cheeses (1058 mg kg −1 ) and by Fiechter et al (2013) in harzer cheese (516 mg kg −1 ). European Food Safety Authority (2011) reported that this amine content can reach, in fresh cheeses 48 mg kg −1 , in hard cheeses 65.5 mg kg −1 , and in acid-curd cheeses 55.3 mg kg −1 ; although much higher amounts were observed in some cheeses—in cheddar 910 mg kg −1 and 140 mg kg −1 in camembert.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…According to Pillonel et al (2003), emmental cheeses contain 8.6–403 mg kg −1 of tyramine. Much higher level of this amine was stated by Standarová et al (2010) in Olomouc cheeses (1058 mg kg −1 ) and by Fiechter et al (2013) in harzer cheese (516 mg kg −1 ). European Food Safety Authority (2011) reported that this amine content can reach, in fresh cheeses 48 mg kg −1 , in hard cheeses 65.5 mg kg −1 , and in acid-curd cheeses 55.3 mg kg −1 ; although much higher amounts were observed in some cheeses—in cheddar 910 mg kg −1 and 140 mg kg −1 in camembert.…”
Section: Resultsmentioning
confidence: 72%
“…According to Fiechter et al (2013), this amine is predominant in harzer cheese and can occur in quantity of 1268 mg kg −1 . Standarová et al (2010) described that Olomouc tvorogs also contained, among other amines, the highest level of cadaverine, up to 2413 mg kg −1 . According to European Food Safety Authority (2011), fresh cheeses can contain from 10.7 to 45 mg kg −1 of cadaverine and the hard cheeses from 47.8 to 83.5 mg kg −1 ; but in some kinds of hard cheeses, the amine level can reach as much as 3170 mg kg −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations